Emergence of Epidural Electrical Stimulation to Facilitate Sensorimotor Network Functionality After Spinal Cord Injury. Issue 3 (6th March 2019) - Calvert, Jonathan S.; Grahn, Peter J.; Zhao, Kristin D.; Lee, Kendall H.
Abstract : Background: Traumatic spinal cord injury (SCI) disrupts signaling pathways between the brain and spinal networks below the level of injury. In cases of severe SCI, permanent loss of sensorimotor and autonomic function can occur. The standard of care for severe SCI uses compensation strategies to maximize independence during activities of daily living while living with chronic SCI‐related dysfunctions. Over the past several years, the research field of spinal neuromodulation has generated promising results that hold potential to enable recovery of functions via epidural electrical stimulation (EES). Methods: This review provides a historical account of the translational research efforts that led to the emergence of EES of the spinal cord to enable intentional control of motor functions that were lost after SCI. We also highlight the major limitations associated with EES after SCI and propose future directions of spinal neuromodulation research. Results: Multiple, independent studies have demonstrated return of motor function via EES in individuals with chronic SCI. These enabled motor functions include intentional, controlled movement of previously paralyzed extremities, independent standing and stepping, and increased grip strength. In addition, improvements in cardiovascular health, respiratory function, body composition, and urologic function have been reported. Conclusions: EES holds promise to enable functions thought to be permanently lost due to SCI. However, EES is currently restricted to scientific investigation in humans with SCI and requires further validation of factors such as safety and efficacy before clinical translation.